STUDI MODEL PENERIMAAN TEHNOLOGI (TECHNOLOGY ACCEPTANCE MODEL) NOVICE ACCOUNTANT - Rustiana Rustiana (KINERJA, 2006)
This study investigates adoption or application of behavior information technologyacceptance. Davis’ Technology Acceptance Model is employed to explain perceived usefulness, perceived ease of use, and intention to use in information systems. The respondents were 228 accounting students in management information system. Data was collected by questionnaire and then analyzed by using linear regression analysis and independent t-test. The results are in line with most of the hypotheses, only hypothesis on gender differences intention to use information system is not supported by the result of the study. It implies that it is useful for managers, developers, and evaluators of information system to consider Technology Acceptance Model.Keywords: perceived usefulness, perceived ease of use, intention to use, information technology